PERANCANGAN SISTEM PENGENDALIAN DOKUMEN REKAM MEDIS DI PUSKESMAS MANGKUBUMI KOTA TASIKMALAYA - Sevia Maysa Shabira; Fadil Ahmad Junaedi (Jurnal Infokes, 2023)
Missfile is something that often happens in the storage room of a health care facility. Efforts to avoid missfile events need to control medical record documents. The Mangkubumi Health Center does not yet have a medical record document control system. The E-Puskesmas NG application does not yet have a feature that can control medical records. This study aims to analyze and design an integrated medical record document control system in the E-Puskesmas NG application. This type of research is qualitative with a FOCUS PDCA approach. How to collect data using interviews and observation. Data analysis using content analysis. The flow of medical record document control starts from the patient coming and being registered, the patient is given a medical record when going to the polyclinic, the medical record is filled out by the polyclinic officer and returned to the storage unit when it is completely filled out. Problems in controlling medical record documents are medical records are lost and scattered due to delays in returning medical records and delays in documenting examination results, there is no SOP as a workflow guideline, expedition records are not made, and there are no medical record personnel with medical record graduates. The proposed medical record document control system design is a reminder system (alert) for filling out medical record documents in the E-Puskesmas NG application which is intended for polyclinic officers when they finish providing services to patients so that they immediately complete documentation and prevent medical record documents from being scattered.